2024
DOI: 10.1038/s41467-024-47096-9
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cell mitochondrial fitness governs chemotherapeutic efficacy in hematologic malignancies

Saeed Daneshmandi,
Jee Eun Choi,
Qi Yan
et al.

Abstract: Myeloid derived suppressor cells (MDSCs) are key regulators of immune responses and correlate with poor outcomes in hematologic malignancies. Here, we identify that MDSC mitochondrial fitness controls the efficacy of doxorubicin chemotherapy in a preclinical lymphoma model. Mechanistically, we show that triggering STAT3 signaling via β2-adrenergic receptor (β2-AR) activation leads to improved MDSC function through metabolic reprograming, marked by sustained mitochondrial respiration and higher ATP generation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Liu et al found that MTERF1 knockdown inhibited colorectal cancer cells proliferation by decreasing in ATP levels and thereby activating p-AMPK/mTOR signaling pathway [29] . A study by Daneshmandi et al showed that induced STAT3 signaling resulted in higher ATP generation, reducing AMPK signalling [30] . Activation of AMPK can inhibit cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al found that MTERF1 knockdown inhibited colorectal cancer cells proliferation by decreasing in ATP levels and thereby activating p-AMPK/mTOR signaling pathway [29] . A study by Daneshmandi et al showed that induced STAT3 signaling resulted in higher ATP generation, reducing AMPK signalling [30] . Activation of AMPK can inhibit cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, lactate accumulation enhances IL-6- and GM-CSF-regulated MDSC generation possibly via the Gi-protein-coupled receptor 81 (GPR81)/mTOR/HIF-1α/STAT3 axis [ 21 , 22 ]. By enhancing MCT-4 expression and the glycolytic rate, lactate promotes M2 polarization by inducing arginase-1 (Arg1), HIF-1α, IL-6, and transcriptional repressors such as ICER, which negatively influence anti-tumor responses [ 23 ]. When stimulated by glycolysis and fibronectin 1 (FN-1), HLA-DR- and CD86-high macrophages exhibit a glycolytic phenotype, impeding the secretion of the anti-tumor agent IL-12 p70 through the PKM2/HIF-1α axis [ 24 , 25 ].…”
Section: Impact Of Dysregulated Glucose Metabolism In the Tmementioning
confidence: 99%